2018
DOI: 10.3389/fimmu.2018.00389
|View full text |Cite
|
Sign up to set email alerts
|

Potential Beneficial Effects of Cytomegalovirus Infection after Transplantation

Abstract: Cytomegalovirus (CMV) infection can cause significant complications after transplantation, but recent emerging data suggest that CMV may paradoxically also exert beneficial effects in two specific allogeneic transplant settings. These potential benefits have been underappreciated and are therefore highlighted in this review. First, after allogeneic hematopoietic stem cell transplantation (HSCT) for acute myeloid leukemia (AML) using T-cell and natural killer (NK) cell-replete grafts, CMV reactivation is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 83 publications
(110 reference statements)
2
45
0
Order By: Relevance
“…However, paradoxical recent data suggest that CMV replication may protect against AML relapse after allo-HSCT [32]. Whether CMV reactivation can protect against relapse after allo-HSCT for other hematological malignancies patients is controversial [33,34]. More research is further needed to better understand these enigmatic observations.…”
Section: Discussionmentioning
confidence: 99%
“…However, paradoxical recent data suggest that CMV replication may protect against AML relapse after allo-HSCT [32]. Whether CMV reactivation can protect against relapse after allo-HSCT for other hematological malignancies patients is controversial [33,34]. More research is further needed to better understand these enigmatic observations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that herpesviruses may, in fact, help fine-tune host immunity. This occurs by modulating one or more types of immune responses to make the host either more resistant or susceptible to other disease situations (Barton et al, 2007 ; White et al, 2010 ; Furman et al, 2015 ; Litjens et al, 2018 ) For example, some studies measured the influence of persisting β-herpesvirus (MCMV) or a γ-herpesvirus (MHV68) infection on the subsequent infection by Listeria monocytogenes and Yersinia pestis . Previously infected mice controlled these infections better than those not infected with MHV68 (Barton et al, 2007 ).…”
Section: Immune System Management By Herpesvirusesmentioning
confidence: 99%
“…Depending on the herpesvirus involved, the outcome of transplantation procedures might vary. For example, HSCT aimed at improving the prognosis of acute myeloid leukemia (AML), induced reactivation of CMV which then expanded a subset of donor derived NKG2C expressing NK cells as well as γδ-T cells of a particular phenotype (Vδ2 −ve γδ-T cells) (Litjens et al, 2018 ). These cells helped control the relapse of leukemic episodes thereby benefiting the host.…”
Section: Immune System Management By Herpesvirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic infection with CMV and the hidden presence of this virus in the body of patients with leukemia and lymphoma have been shown to produce specific natural killer (NK) cells . After bone marrow transplantation, these specific immune cells, by inhibiting the remaining cancerous cells, have prevent the recurrence of leukemia and even reduce the development of graft versus host disease (GVHD) . A study showed that prolonged CMV protects its host against bacterial infection, which has been proven in the rat model.…”
Section: Two‐sided Communication Between the Virus And The Host (Mutumentioning
confidence: 99%